Dampak Proyek Pengadaan Bibit Jagung di Bima: Kajian Kritis Prespektif the Panoptic View: A Discourse Approach to Communication and Development - Dwi Ghina Mardiah; Makroen Sanjaya; Faisal Bakti; Tantan Hermasah; Mayadah El Hawani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The problem in the corn seed procurement project has escalated into a disaster for the Bima region. According to data from the Head of the Agricultural Office, the Bima area has a total of 202,000 hectares of forest area, of which 58,000 hectares have been converted into corn farmland. Over the past ten years, the Government of West Nusa Tenggara (NTB) has promoted a corn planting program. High corn prices, followed by the emergence of corn purchasing warehouses, as well as assistance in the form of seeds and fertilizers, have encouraged farmers to compete in planting corn. The purpose of this study is to encourage the government and farmers to pay greater attention to land management for corn cultivation, soil and water conservation, land suitability and land capability, while maintaining environmental sustainability in order to address the recurring problem of annual flash floods. This research employs the theory of the panoptic perspective, a discourse approach to communication and development by Jan Servaes, involving three theoretical concepts, as well as three scientific concepts derived from the concept of mufsid in the Qur’an, Surah Al-A’raf verse 56, along with two additional concepts. The study adopts a critical paradigm with a qualitative research design, using approaches from communication studies, social sciences, and geography. Data collection and analysis methods combine in-depth interviews, literature review, and data and source triangulation. The results of the analysis show that the government program of providing free corn seeds by the Minister of Agriculture and the massive expansion of corn cultivation have led to uncontrolled land conversion. Of the total 250,000 hectares of protected forest area in Bima, approximately 75% has been planted with corn. The conclusion of this study indicates that the government appears to have turned a blind eye to the environmental impacts generated. Therefore, the government must continue and strengthen supervision of the programs it initiates so that they do not damage the environment or erode the cultural values of the Bima region, and not merely prioritize economic profit.